Types of anti-phishing solutions for phishing attack - Siti Hawa, Apandi; Jamaludin, Sallim; Roslina, Mohd Sidek (IOP Publishing Ltd, 2020)
Nowadays, many people use Internet to do online activity. This scenario exposed them to danger in Internet which is phishing attack. In order to solve phishing attack, the anti-phishing solutions are needed. Based on our review, there are still lacks of articles that review on the types of anti-phishing solutions in detail. In this paper, a general idea of phishing attack and anti-phishing solutions is presented. The phishing attack can be classified into two categories which are social engineering and malware-based phishing attack. The anti-phishing solutions can be differentiating into two types which are phishing prevention and phishing detection. Compared to phishing prevention, the phishing detection is more important to solve the phishing attack. In phishing detection, there are two categories which are user awareness and software detection. The software detection has two methods which are traditional and automatic. There are two types for automatic method of software detection which are public phishing detection toolbars and academic phishing detection / classification schemes. Based on the comparison of all types of phishing detection, the academic phishing detection / classification schemes are more useful for phishing detection. For future work, we can do more research on the academic phishing detection / classification schemes that utilize deep learning to see its potential of accuracy to detect phishing websites.